American culture and the media reading, writing, thinking - Cassebaum, Anne; Haskell, Rosemary (Boston Houghton Mifflin, 1997)
[The book] is based on [the author's] belief that reading and writing skills are best taught together and in the context of high-interest subject matter. In section I, the mass media ... form a familiar and reassuring, yet rich and complex, subject for exploration and analysis. Section II, the rhetoric and brief handbook, gives advice and information for students to use as they work on their papers.... Fifty thematically unified high-interest readings in section I. -Pref.
Reading and writing about American culture and the media: Shaping forces, culture and mass media; Work; Diversity; Gender roles; Sports; Poverty and wealth; Violence; Environment -- Working on your paper, a guide to writing: Coming up with ideas; Keeping a journal; Making the most of your reading; Analysis, going deeper to come up with ideas; Interviewing, using other people's brains; Working the library; Organizing, getting your ideas together; Writing the first draft; Revising; Getting and giving good criticism; Editing, the final polish; Writing on the spot; Making gains for the next paper.
Keywords: Mass media and culture -- United States; College readers; English language -- Rhetoric